Pengaruh Tingkat Pendapatan Orang Tua Terhadap Pendidikan Anak - Aisyah (PT. Pubsains Nur Cendekia, 2024)
Education is a necessity in human life. This process continues throughout life and is achieved through three ways: formal education, non-formal education, and non-informal education. The social status of parents (income level) is very important for children’s education. A family with a good income level not only fulfills daily needs such as meeting children's educational needs but of course also influences the development of attention to daily needs, including the education needs of their children. This study aims to find out the impact of parents' income rates on children's education. The research method used is a library survey. The results of this study show that parents' income rates influence their children's education. Several other factors influence, such as parents' educational levels, children's abilities, and other external factors. However, the results of this study show that the influence of parents' income rates on children's education dominates.